Síntese de octaidroacridinas funcionalizadas a partir da reação do citronelal ou de 3-tioorganoilcitronelal com arilaminas - Silva, Márcio Santos da (2008)
In this work, we present a simple solvent-free one-pot imine-Diels-Alder reaction of 3-thioorganylcitronellal and arylamines using solid supported catalyst (SiO2/ZnCl2) at room temperature (Scheme 1). This general, efficient and improved method is selective, affording preferentially new trans-3- thioorganyloctahydroacridines (S-OHAs) in good yields. The use of microwave irradiation facilitates the procedure and accelerates the reaction. We also make the reaction of (R)-citronellal with functionalized arylamines at room temperature.